A comprehensive comparison of the static performance of commercial GaN-on-Si devices - Perkins, Samuel; Arvanitopoulos, A.; Gyftakis, K. N.; Lophitis, Neophytos (My University, 2017)
Gallium Nitride (GaN) based devices on Silicon (Si) substrates (GaN-on-Si) promise unmatched performance at low cost. Despite this theoretical promise, the lattice and thermal conductivity mismatch between the GaN and Si has obstructed the realization of reliable electrically graded high voltage devices. Recently, a small number of manufacturers have claimed the successful development of such devices. Panasonic and Transphorm among a few others have also made their devices available in the open market. The commercial availability of these devices, (something common only for mature technologies), proves the remarkable progress that has been achieved. In this paper, a comprehensive and experimentally derived comparison of the static performance is made between the 600 V Panasonic PGA26C09DV Gate Injected Transistor (GIT) and the 600 V Transphorm cascode TO-220 series devices. The Si 650 V Infineon SPA15N60C3 Super-Junction (S-J) provides a reference with Si technology. The Panasonic devices feature a p-GaN layer which makes them one of the first Enhancement mode (E-mode) GaN power devices on the market, whereas the Transphorm devices are Depletion-mode (D-mode) High Electron Mobility Transistors (HEMTs) cascaded with a low voltage (LV) Si Metal Oxide Semiconductor Field Effect Transistor (MOSFET). Despite the Panasonic and Transphorm devices being examples of GaN-on-Si aiming for the same applications, the measurements and analysis shows that their performance is very different.
Keywords: B1505A; cascode GaN; E-mode; GaN HEMT; power devices; static performance